Ongoing Ostomy Self-Care Challenges of Long-Term Rectal Cancer Survivors - Bulkley, Joanna E. (Support Care Cancer, 2018)
PURPOSE: Surgical treatment for rectal cancer (RC) can result in an intestinal ostomy that requires lifelong adaptation and investment of physical, cognitive, and financial resources. However, little is known about the extent of ongoing challenges related to ostomy self-care among long-term RC survivors. We analyzed the prevalence of self-reported ostomy self-care challenges and the physical and environmental factors that can support or undermine ostomy self-care. METHODS: We mailed surveys to long-term (≥5 years post-diagnosis) RC survivors, including 177 adults with ostomies who were members of integrated health systems in northern California, Oregon, and Washington State. Potential participants were identified through tumor registries. Data were also extracted from electronic health records. RESULTS: The response rate was 66%. The majority of respondents were male (67%) and the mean age was 75 years. Sixty-three percent of respondents reported at least one ostomy self-care challenge. The most common challenges were leakage or skin problems around the ostomy and needing to change the pouching system too frequently. Twenty-two percent reported difficulty caring for their ostomy. Younger age and higher BMI were consistently related to ostomy self-care challenges. CONCLUSIONS: The majority of RC survivors reported ostomy-related self-care challenges and 31% experienced problems across multiple domains of ostomy self-care. In addition, most survivors reported significant physical challenges that could lead to ostomy-related disability. Although the participants surveyed had access to ostomy care nurses, the care gaps we found suggest additional work is needed to understand barriers to ostomy care, reduce unmet needs, and improve well-being among this group.